GABA(B) Receptors Regulate Extrasynaptic GABA(A) Receptors - Connelly, William M. (Society for Neuroscience, 2013)
Tonic inhibitory GABA(A) receptor-mediated currents are observed in numerous cell types in the CNS, including thalamocortical neurons of the ventrobasal thalamus, dentate gyrus granule cells, and cerebellar granule cells. Here we show that in rat brain slices, activation of postsynaptic GABA(B) receptors enhances the magnitude of the tonic GABA(A) current recorded in these cell types via a pathway involving G(i/o) G proteins, adenylate cyclase, and cAMP-dependent protein kinase. Using a combination of pharmacology and knockout mice, we show that this pathway is independent of potassium channels or GABA transporters. Furthermore, the enhancement in tonic current is sufficient to significantly alter the excitability of thalamocortical neurons. These results demonstrate for the first time a postsynaptic crosstalk between GABA(B) and GABA(A) receptors.